Crime and art: sociological and criminological perspectives of crimes in the art world - Oosterman, Naomi; Yates, Donna (Studies in art, heritage, law and the market, 2021)
"This volume brings together work by authors who draw upon sociological and criminological methods, theory, and frameworks, to produce research that pushes boundaries, considers new questions, and reshape the existing understanding of 'art crimes', with a strong emphasis on methodological innovation and novel theory application"--Page 4 of cover